Book Scientist Nojus Feigelmanas (1918–2002) - Mozūras, Dovydas (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]Nojus Feigelmanas is a bibliographer and a librarian known for his significant contribution to the history of Lithuanian culture. Consistent and targeted book-related activities pursued by Feigelmanas throughout his life-span have earned him the status of a bookscientist. He was born in Panevėžys on 8 February, 1918. During the period of 1931-1936 he studied in the private Panevėžys Jewish Gymnasium. In 1936-1940 he studied geodesy at Vytautas Magnus University, but failed to complete his studies as he was called up to the army when World War II was launched. In 1959, N. Feigelmanas graduated the Faculty of History and Philology at Vilnius University. In 1950-1990, he worked at the Vilnius University Library: having started career as a bibliographer, he became Head of the Rare Print Department and retained this position for more than three decades. Later in life, in 1990, he moved to Israel and died there on 7 September, 2002, in the city of Ashkelon. The printed catalogues compiled by N. Feigelman are as follows: “The Old Lithuanian Book at Vilnius University” (1959), “The Incunabula of Lithuania” (1975), “The paleotypes of Vilnius University Library” (2003, posthumously, co-authored). He has also published three dozen scientific articles, organized scientific exhibitions, cultural programs on television, etc.The article aims at disclosing N. Feigelmanas’s path toward book science and his contribution to the development of Lithuanian book science. It also identifies the key factors that have shaped his personality, the choice of the librarian’s profession which ignited his interest in book study, and analyses the directories compiled by N. Feigelmanas and the scientific articles. The conclusion has been drawn that during his long life, from the very young days, when he first read Torah at school, visited book fairs and exhibitions as a gymnasium student, throughout his career at the scientific Vytautas Magnus University Library and small military libraries, to the end of his life, even after he emigrated to Israel – the book remained his lifelong companion.
Keywords: Nojus Feigelmanas, book science, the old Lithuanian book, incunabula, paleotypes, Vilnius University, Vilniaus University Library, catalogues, Lithuanian Jews